The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.5505/pajes.2018.72246
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of concrete to concrete interfaces under uniaxial and shear forces

Abstract: ÖzThis research aims to evaluate the bond strength between normal strength substrate concrete and different types of high strength overlay concretes. In order to obtain different characteristics in the overlay concrete, silica fume and steel fibers were used. The slant shear and bisurface shear tests were conducted to quantify the effect of different high strength concrete compositions on the bond strength. The mechanical properties of overlay/substrate concrete composites were also analysed on cylindrical sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Chen et al tested the bond strength of UHPC with a steel fiber volume fraction of 0-2.5%; bond strength increased with fiber content increase (CHEN et al, 2021). Kabay et al also found that with steel fiber mixed, tensile strength increased 17% (KABAY and KIZILKANAT, 2018). On the other hand, some researchers pointed out that due to UHPC and old concrete existing in a layer of mortar, fibers do not affect the bonding interface directly (HABER et al, 2018).…”
Section: Ultra-high Performance Concretementioning
confidence: 99%
“…Chen et al tested the bond strength of UHPC with a steel fiber volume fraction of 0-2.5%; bond strength increased with fiber content increase (CHEN et al, 2021). Kabay et al also found that with steel fiber mixed, tensile strength increased 17% (KABAY and KIZILKANAT, 2018). On the other hand, some researchers pointed out that due to UHPC and old concrete existing in a layer of mortar, fibers do not affect the bonding interface directly (HABER et al, 2018).…”
Section: Ultra-high Performance Concretementioning
confidence: 99%
“…Pure shear stress is assumed to act between the substrate and repair layers in the pure shear test. Various tests are available to determine interface shear strength, like torsion shear test (2), push through cube test (7), BSST (60)(61)(62), modified vertical shear test (57) (61), DST (63), and a mixed-mode of them.…”
Section: Pure Shear Testsmentioning
confidence: 99%